http://isrctn.com/ 2015
DOI: 10.1186/isrctn13033050
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Initiated by Employer and its health effects: an eight-week follow-up study

Abstract: Background: While the health benefits of physical activity are well established, little is known about health effects of physical activity programs initiated by employer. Methods: Background data and level of physical activity were collected by questionnaire among 78 men and 43 women working in road maintenance pre and post an 8-week physical activity motivational program. As a part of the program steps measured by accelerometer were registered online where team and individual performances could be continuousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 18 publications
0
20
1
Order By: Relevance
“…Fasting insulin concentration was significantly lower in men and women that fit both the HP and PA3 (HP+PA3) categories (> 1.11 g/kg/d and >3.2 km/d) compared to LP+PA1 (≤ 0.91 g/kg/d and ≤ 0.8 km/d), which supports previous research suggesting the importance of increased PA for improving insulin regulation [43]. However, in the present study, higher PA was also associated with significantly higher LDL-cholesterol, which contradicts previous findings [44]. The associations between protein intake and PA level with cardiometabolic health observed in this study raise interesting questions in regard to whether diet or PA is the primary regulator cardiometabolic health.…”
Section: Discussioncontrasting
confidence: 53%
“…Fasting insulin concentration was significantly lower in men and women that fit both the HP and PA3 (HP+PA3) categories (> 1.11 g/kg/d and >3.2 km/d) compared to LP+PA1 (≤ 0.91 g/kg/d and ≤ 0.8 km/d), which supports previous research suggesting the importance of increased PA for improving insulin regulation [43]. However, in the present study, higher PA was also associated with significantly higher LDL-cholesterol, which contradicts previous findings [44]. The associations between protein intake and PA level with cardiometabolic health observed in this study raise interesting questions in regard to whether diet or PA is the primary regulator cardiometabolic health.…”
Section: Discussioncontrasting
confidence: 53%
“…The full text was obtained for 71 publications; of these, 18 publications describing 15 studies met the criteria for inclusion. 3754 An updated search to February 2018 found an additional five publications describing four studies, 5559 and a second updated search to December 2018 found an additional seven publications for six studies, 6066 resulting in a total of 30 publications (25 studies) for inclusion in the review.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies were conducted in the USA, 4246,50,53,57,59,60,62 five in Australia, 37,38,49,55,56,61,66 two in Canada, 58,63 two in the Netherlands, 52,54 one in Belgium, 64,65 Singapore, 39,40 Finland, 47,48 Norway, 51 and one in multiple countries. 41 Workplace settings included academic and academic medical institutions, 42–44,50,53,57,59,60,62 healthcare, 63,66 health insurance, 45,49 wellbeing improvement, 46 property and infrastructure, 37,38 pension insurance, 47,48 financial services, 61 road maintenance, 51 and haulage. 55,56 Six studies targeted multiple organisations.…”
Section: Resultsmentioning
confidence: 99%
“…Additional strengths were the inclusion of multiple outcomes (including both objective and self-reported measures of PA) and the capture of data at multiple time points, which enabled a more detailed exploration of impact and acceptability of the intervention. Furthermore, the study was of relatively long duration with follow-up at eight months; previous studies of mHealth interventions for PA in other workplace settings have been characterised by short-term interventions and follow-up, generally less than six months (22)(23)(24)(25)(26)(27)(28)(29)(30). The high ecological validity of this study, conducted in a real-world setting, and the relatively large, diverse and representative sample of o cers and staff (including both urban and rural sites) should also be recognised.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Despite its considerable potential, there are many gaps in our understanding of how mHealth technology may be utilised to change behaviour and its potential impact on health outcomes. Systematic reviews have found mHealth studies to be characterised by short-term interventions and follow-up (18)(19)(20)(21), with follow-up typically six months or less (22)(23)(24)(25) and often only a few weeks (26)(27)(28)(29)(30) in duration. Aspects such as feasibility, acceptability and engagement are of vital importance, but remain understudied in mHealth research (31).…”
Section: Introductionmentioning
confidence: 99%